A construção da experiência espiritual e sua problematização como lugar de superação dos limites do paradigma biomédico: uma contribuição para a reflexão sobre espiritualidade na educação médica. - Oliveira, Eliane Silva de (2008)
This thesis presents a qualitative research about the development of the spiritual experience and it’s problematization on how overcoming the limits of the biomedical paradigm, and proposes to contribute on the reflection about spirituality in medical education in three situations: the context in which the mothers of opt to use transcendental explanations for their experiences in the Nursery Mother Kangaroo in the hospital Maternidade Escola Assis Chateaubriand; along subjects who search for an specific group of people, prayers, in the Family Health Program Novo Iracema, in Maranguape; and through the narratives of subjects who have gone through near-death experiences and near-death simile (out-of-body experience). The research uses as thematic methodology the oral history (an anthropologic method of research – individual science), using semi-structured interviews, with transdiciplinary approach , in a multireferential perspective, which were meant as an attempt at a plural reading, using distinct reference systems; obtaining the narratives of the subjects of the subjects about their reflections over the development of the spiritual experience throughout the processes of ailment and cure; proposing to study what these experiences point as a perspective of overcoming limits of the biomedical paradigm. The narratives were recorded, transcripted and analyzed, according to the theoretical references of this thesis: science of education, medical science and the spiritist theory in it’s religious aspect, philosophical and scientific. The analysis presented in the course of this study lead to the understanding: of the need for a new concept for the human being (as an spiritual being); of the need to consider the symbolic productions that alludes to a transcendental dimension, considering the spiritual phenomena which must be taken under consideration in medicine. The near-death experiences, and the out-of-body experiences suggest the existence of an out-of-body individuality, conscious, with identity, intelligence, memory, with transcendental abilities, capable of having experiences with other spiritual beings, which must be considered in the medical practice, especially in the relationship doctor-patient with subjects in coma and close to death and rethink the reanimation period and he criteria used to establish the success of these maneuvers; that of multireferential study utilizing the sipiritist theory, in the religious perspective, philosophical and scientific should be made, developing the medical-spiritist paradigm as a relative contribution for medicine